CYCLIC SCHEDULE RESEARCH FOR THE MODEL OF REAL-TIME DYNAMIC NETWORK OBJECT - Svjatnij, V. A.; Ivanov, A. Y; Ivanov, Y. A. (Radio Electronics, Computer Science, Control, 2018)
Context. Development of models of automated control systems for ventilation, designed to prevent emergencies in the mine ventilation network, is considered in the paper. The task of research and implementation of software modeling tools that allows the execution of experiments with real science-intensive objects is being solved. Objective is to improve effectiveness of the real-time model of a mine ventilation network by developing and optimizing a method for organizing a computational process that considers the different frequency parameters of the models. Method. We proposed and investigated the algorithm of scheduling and implementation of the cyclic schedule for the model of the dynamic real-time object, presented by the mine ventilation network. We analyzed the mathematical model of aerodynamic processes and classified it as a stiff real-time system. Calculations of phase variables with varying velocities are performed by splitting the original algorithm into parallel flows in the program model. Numerical integration of the differential equations system of the mathematical model of the object is performed in accordance with the algorithm of static priorities and controlled using the time scale. The schedules feasibility is determined for the target object limited parameters. The scheduling algorithm considers the time parameters of software tools for both uniprocessor and symmetric multiprocessor systems. Results. Analysis of simulation results of the proposed model with using cyclic schedules shows the correspondence of the obtained modeling results to the reference one. Conclusions. The main advantage of the model is the performance increase when performing data processing due to the reduction of the CPU usage time. Implemented cyclic schedule algorithm for real-time simulation platform can be used for development of control system for technological and emergency modes of ventilation in mines.